Lanthanoid Biphenolates as a Rich Source of Lanthanoid‐Main Group Heterobimetallic Complexes. Issue 5 (27th January 2022) - Ali, Safaa H.; Shephard, Angus C. G.; Wang, Jun; Guo, Zhifang; Davies, Murray S.; Deacon, Glen B.; Junk, Peter C.
Abstract: Several new trivalent dinuclear rare earth 2, 2'‐methylenebis(6‐ tert ‐butyl‐4‐methylphenolate) (mbmp 2− ) complexes with the general form [Ln2 (mbmp)3 (thf)n ] (Ln=Sm 1, Tb 2 (n=3), and Ho 3, Yb 4 (n=2), and a tetravalent cerium complex [Ce(mbmp)2 (thf)2 ] (5) have been synthesised by RTP (redox transmetallation/protolysis) reactions from lanthanoid metals, Hg(C6 F5 )2 and the biphenol mbmpH2 . These new complexes and some previously reported partially protonated rare earth biphenolate complexes [Ln(mbmp)(mbmpH)(thf)n ] react with lithium, aluminium, potassium and zinc organometallic reagents to form lanthanoid‐main group heterobimetallic species. When reaction mixtures containing the Ln biphenolate complexes were treated with n ‐butyllithium, both molecular ([Li(thf)2 Ln(mbmp)2 (thf)n ] (Ln=La 6, Pr 7 (n=2) and Er 8, Yb 9, and Lu 10 (n=1)) and charge separated ([Li(thf)4 ][Ln(mbmp)2 (thf)2 ] (Ln=Y 11, Sm 12, Dy 13, and Ho 14) complexes were isolated. Treatment with trimethylaluminium also led to isolation of molecular ([AlMe2 Ln(mbmp)2 (thf)2 ] (Ln=Pr 15, Sm 16, and Tb 17)) and ionic [La(mbmp)(thf)5 ][AlMe2 (mbmp)] (18) complexes. One gadolinium‐potassium ([K(thf)3 Gd(mbmp)2 (thf)2 ] (19)), and one ytterbium‐zinc species ([ZnEtYb(mbmp)2 (thf)] (20)) were isolated from treatment of reaction mixtures with potassium bis(trimethylsilyl)amide and diethylzinc respectively. Abstract : Trivalent dinuclear rare earth 2, 2′‐methylenebis(6‐tert‐butyl‐4‐methylphenolate) (mbmp 2‐ ) complexes with the general form [Ln2 (mbmp)3 (thf)n ] react with lithium, aluminium, potassium and zinc organometallic reagents to form lanthanoid‐main group heterobimetallic species.